1989
DOI: 10.1128/jb.171.7.3973-3981.1989
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of members of a cyanobacterial psbA gene family in response to light

Abstract: The genome of the cyanobacterium Synechococcus sp. strain PCC 7942 contains three psbA genes encoding two forms of the Dl protein: form I, the product of psbAI, differs from form II, the product of both psbAII and psbAIII, at 25 of 360 residues. DI is essential for photosynthesis as a core component of the photosystem II reaction center. Translational gene fusions between each of the Synechococcus psbA genes and the Escherichia coli lacZ gene were inserted into the chromosome of wild-type Synechococcus sp. at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 25 publications
7
97
0
Order By: Relevance
“…In 2005, the lowest psbA1 transcript levels were observed during the highlight mid-day periods, whereas highest levels were observed under low irradiance in the late afternoon to early evening and in the early morning (Figure 5b). Our in situ results are consistent with culture studies of Syn OS-B 0 , where psbA2/3 transcript levels increased during the transition from low-to-high light, whereas psbA1 transcript levels increased when the cells were shifted from high-to-low light (Kilian et al, 2007); similar results were reported for other cultivated cyanobacteria (Schaefer and Golden, 1989).…”
Section: Photosynthesissupporting
confidence: 81%
“…In 2005, the lowest psbA1 transcript levels were observed during the highlight mid-day periods, whereas highest levels were observed under low irradiance in the late afternoon to early evening and in the early morning (Figure 5b). Our in situ results are consistent with culture studies of Syn OS-B 0 , where psbA2/3 transcript levels increased during the transition from low-to-high light, whereas psbA1 transcript levels increased when the cells were shifted from high-to-low light (Kilian et al, 2007); similar results were reported for other cultivated cyanobacteria (Schaefer and Golden, 1989).…”
Section: Photosynthesissupporting
confidence: 81%
“…Transcription of psbA, encoding the D1 protein of PS I1 in Synechococcus sp., occurs during periods of illumination (Schaffer & Golden 1989). Similarly, the chlorophyll binding protein, cab, mRNA levels are elevated during the dark period in Dunaliella sp.…”
Section: Discussionmentioning
confidence: 91%
“…One intriguing question that remains to be solved is whether the multiple pcb gene copies are expressed differentially depending on the light conditions, as was previously shown for the different copies of psbA (17) and psbD (18) …”
Section: Discussionmentioning
confidence: 99%